FINANCIAL FEASIBILITY ANALYSIS OF PEPPER FARMING IN NORTH LAMPUNG REGENCY OF LAMPUNG PROVINCE INDONESIA - Suryani A. (Russian Journal of Agricultural and Socio-Economic Sciences, 2019)
This research was aimed at investigating the profitability and feasibility of pepper farming, which was conducted in North Lampung Regency of Lampung Province. The data were collected from November 2014 – February 2015 from 53 farmer respondents. This research used both primary and secondary data. The former was collected through survey by using questionnaires and interview with the farmers, while the latter was collected from the research-related institutions. The data were then analyzed through financial analysis including profit analysis, R/C ratio, B/C ratio, Net Present Value (NPV), and Internal Rate of Return (IRR). The results show that pepper farmings are profitable with R/C ratio of 5.98 and B/C ratio of 4.98 which are feasible to develop with the NPV value of Rp. 177.403.489,66. The Net B/C which was obtained from the calculation of the 15-year pepper farming is 10.87 with an IRR of 75%.